ANALISIS HUBUNGAN KEKERABATAN CEMPEDAK (Artocarpus champaden Lour.) BERDASARKAN PENANDA MORFOLOGI DI KABUPATEN KAMPAR PROVINSI RIAU - Via Andani; Fitmawati '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Kampar is one of the regency in Riau Province that has high diversity of cempedak (Artocarpus champaden Lour.). The diversity of cempedak in Kampar have not been reported, researched and characterized morphologically. This research was aimed to analyze the diversity of cempedak cultivars from various regions. This study had been conducted from September to Desember 2013, using exploration method. A total of 51 morphological characters from 30 individuals were observed and scored and then analyzed using NTSYSpc 2.02 and Minitab 16.0. Four cempedak cultivars identified in this study were Bubur (6 individuals), Hutan (14 individuals), Langkat (5 individuals), and Nangkadak (5 individuals). The coeffisien similarity were range from 0.23 to 0.72. The dendogram shows two main group, first group consist of 29 individuals, such as Bubur (5 individuals), Hutan (14 individuals), Langkat (5 individuals) and Nangkadak (5 individuals); the second group consisted of 1 individu (Bubur cultivar). Main group analysis showed that plant clustered is not based on the origin. Furthermore pearsoncorrelation analysis on 51 characters showed that there are positive correlations between 40 characters, and negative correlations between 6 characters.